GROWTH PHASE OF ISOCHRYSIS GALBANA NATURAL FEED WITH DIFFERENT CULTURE MEDIA VOLUMES ON LABORATORY SCALE - Laily Fitriani Mulyani; Nuri Muahiddah; Thoy Batun Citra Rahmadani (Jurnal Perikanan Unram, 2024)
One of the causes of low growth and survival in the early development of larvae that still rely on food from natural feed is the availability of feed. The purpose of this study was to analyze the percentage level of increase in the density of the amount of natural feed cultured in Erlenmeyer media with different volumes of culture media. Completely Randomized Design with 3 treatments and 5 replications. The treatments used were 500 ml, 1000 ml and 5000 ml culture media volumes. The results of the study showed that the 500 ml volume culture media produced a density increase of 20%, then for the 1000 ml volume culture media it produced a density increase of 16% and for the 5000 ml volume culture media it produced an increase in density of 8%. So that with a 500 ml volume culture media it can effectively increase the density of I. galbana.